Job satisfaction of Slovenian hospital nursing workforce. (22nd July 2013) - Prosen, Mirko; Piskar, Franka
<x xml:space="preserve">Abstract</x> Aim To test the psychometric properties of the McCloskey–Mueller Satisfaction Scale and to assess which of the McCloskey–Mueller Satisfaction Scale dimensionalities have a considerable impact on job satisfaction of nursing employees in three public Slovenian hospitals. Background Job satisfaction of nurses is linked to productivity, turnover, absenteeism and patient outcomes. Little is known about the factors contributing to job satisfaction among Slovenian hospital nurses. Understanding the contributing factors could help nurse managers to take appropriate measures. Method A cross‐sectional survey study was used to obtain a sample of 169 registered nursing assistants and 74 registered nurses working in three public hospitals in Slovenia, from which data was obtained using the McCloskey–Mueller Satisfaction Scale. Dimensionality was tested using exploratory factor analysis. Results A seven‐factor structure of 29 items was obtained, which accounted for 54.3% of the total variance in job satisfaction, and was internally consistent (Cronbach's alpha coefficient of the instrument was 0.78). The first factor 'Satisfaction with Interaction Opportunities', which is a component of the social rewards dimension in the McCloskey–Mueller Satisfaction Scale, explained 30.6% of the variation. Conclusion The registered nursing assistants' job dissatisfaction was higher than that of the registered nurses. Both were mostly dissatisfied with professional opportunities. Using the factor analysis, a seven‐factor structure was found instead of the originally introduced eight‐factor model, which suggests a need for further redevelopment of the McCloskey–Mueller Satisfaction Scale. Implications for nursing management The results suggest that operational management needs to revitalize the work environment by ensuring proactive leadership and allowing participation in the decision‐making process, while health‐care organisations need to support the professional development of registered nursing assistants and registered nurses in order to achieve sustainable effects in job satisfaction.